2011
DOI: 10.1007/s00262-011-1052-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of cytoplasmic melanoma-associated antigen at diagnosis may predict clinical relapse in neuroblastoma patients

Abstract: The high molecular weight melanoma-associated antigen (HMW-MAA) and the cytoplasmic melanoma-associated antigen (cyt-MAA/LGALS3BP) are expressed in melanoma. Their serum levels are increased in melanoma patients and correlate with clinical outcome. We investigated whether these molecules can serve as prognostic markers for neuroblastoma (NB) patients. Expression of cyt-MAA and HMW-MAA was evaluated by flow cytometry in NB cell lines, patients’ neuroblasts (FI-NB), and short-term cultures of these latter cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…MDA-MB 435 accumulates high concentrations of extracellular LGALS3BP compared to other cancer cell lines (110), and patients with metastatic melanoma have higher serum LGALS3BP than patients with benign skin cancer (111). In patients with breast cancer (112, 113), ovarian cancer (114117), or melanoma (118120), serum LGALS3BP concentrations increase during the progression to metastasis (49, 121). An intriguing possibility is that LGALS3BP may play a role in metastasis by inhibiting monocyte-derived fibrocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…MDA-MB 435 accumulates high concentrations of extracellular LGALS3BP compared to other cancer cell lines (110), and patients with metastatic melanoma have higher serum LGALS3BP than patients with benign skin cancer (111). In patients with breast cancer (112, 113), ovarian cancer (114117), or melanoma (118120), serum LGALS3BP concentrations increase during the progression to metastasis (49, 121). An intriguing possibility is that LGALS3BP may play a role in metastasis by inhibiting monocyte-derived fibrocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…If not completely destroyed in the extracellular spaces, NG2/CSPG4 fragments may eventually enter the blood stream. In fact, such fragments are frequently found in peripheral blood of cancer patients for whom they may serve as an adjunct in the prognostication of the disease (65,66).…”
Section: Bidirectional Metalloproteinase-dependent Interactions Of Thmentioning
confidence: 99%
“…Moreover, high serum levels of sHLA-G and CYT-MAA at diagnosis predicted a worse event-free survival (EFS), thus suggesting a potential use of these molecules as surrogate biomarkers [4, 5]. We have also demonstrated that high levels of DKK-1 associate with poor clinical response [6] and high VMA/HVA ratio associated with a better EFS, but only in patients with localized MYCN nonamplified tumors [7].…”
Section: Introductionmentioning
confidence: 99%